An In-Depth Investigation of Dental Age Assessment in the Mardan Population: Employing the Kvaal Technique Via Digital Panoramic Radiography Analysis (Medical Forum Monthly, 2023)
Objective: This study aimed to assess the accuracy of the Kvaal technique in estimating dental age using digital panoramic radiography within the Mardan demographic.Study Design: A cross-sectional observational studyPlace and Duration of Study: This study was conducted at the Department of Oral Biology, Bacha Khan Medical College Mardan from 28th December 2018 to 28th May 2019.Materials and Methods: Digital panoramic radiographs were obtained following a standard protocol. Measurements of pulp chamber dimensions were performed using the Kvaal technique. Two independent examiners conducted the measurements, and data were analyzed using SPSS version 27.0.Results: The study revealed that the Kvaal technique had a high correlation (r=0.708) with the chronological age, with the ratios 'M' and 'W-L' being the most significantly correlated variables. The technique proved to be more accurate across a broader age range in the Mardan population.Conclusion: The research underscores the effectiveness of the Kvaal technique in estimating dental age through digital panoramic radiography for the Mardan demographic. A significant correlation was observed between the Kvaal measurements and the actual chronological age, particularly with the 'M' and 'W-L' ratios. This suggests that the Kvaal method holds potential for reliable dental age estimation in the Mardan population, proving its importance in forensic, legal, and clinical scenarios.